Developing Innovative Educational Assessment Practices for the 21st Century: A Study on Formative, Summative, and Adaptive Testing - Dr. Zahid Hussain Sahito; Dr. Farzana Jabeen Khoso; Dr. Ghulam Ali Kerio (Review Journal of Social Psychology & Social Works, 2025)
Individuals are interested in the outcomes of this inquiry regarding educational assessment, particularly the changes in formative, summative, and adaptive assessment approaches in the 21st century, in terms of their efficacy, student engagement, and fairness. Cross-sectional surveys were conducted on 500 students and faculty members in various education contexts with the help of a combination of quantitative and qualitative data. Therefore, based on the results, adaptive assessments, which change across the learning process depending on students’ abilities, show the highest level of effectiveness and learners’ engagement, emphasizing the personalization of the learning process and the absence of test-related anxieties. Feedback-oriented formative assessments ensure ongoing learning and engagement from assisting in helping students and other learners improve their performance. On the other hand, the summative tests as imperative for the assessment purpose lack the pedagogy in pinpointing the thinking skills and providing equal chances. Some of the difficulties may entail technological hurdles, inadequate preparation of teachers, and scarcities of resources and personnel; thus, the study advocates for more focused interventions to enhance the usage of enhanced procedures. The research therefore aligns the findings with current literature on the possibility of adopting a formative, summative, and adaptive assessment integration model to develop fair, inclusive, and effective learning environments for learners. Theoretical and practical implications for policy and practice along with directions for further research are considered in the context of the findings, stressing the need for educator, policymaker, and technologist cooperation to optimize the potential of state of the art practices in assessment.